Assessing Connectedness to Water as a Catalyst for Change: A Multidimensional Approach to Extension Education on Water Conservation - John M. Diaz; Laura Warner (Journal of International Agricultural and Extension Education, 2024)
As issues of water security remain pervasive, extension educators continue to search for strategies to promote water conservation. Social marketing represents such a strategy that can be leveraged as a tool to better understand target audiences and develop strategic communication campaigns to promote practice adoption and behavior change. Research demonstrates that social marketing efforts that focus on understanding and developing personal norms and values hold promise for increasing the implementation of residential conservation behaviors. The construct of Connectedness to Nature is one strategy for developing environmentally aligned personal norms. This study leverages a similar concept, connectedness to water, to understand how an emotional connection to water creates values that promote water conservation. We take an audience segmentation approach to understand how water conservation relates to connection to water, sociodemographic characteristics, and future conservation intentions. We conducted cluster analysis to identify audience segments followed by ANOVAs and Chi-Square tests to determine significant variations among the segments. We found that the strongest effect size was associated with connectedness to water. Interestingly, the higher an individual’s connection to water, the higher the degree to which they were engaged with water conservation practices. This relationship represents an opportunity to tailor relevant extension education strategies to focus on the advancement of an individual’s personal connections to water and perpetuate an enhanced sense of personal obligation to conserve.
Keywords: Concise Connectedness to Water Scale; Behavior Change; Water Conservation; Audience Analysis; Cluster Analysis